PLANET: A radial layout algorithm for network visualization - Ge Huang; Yong Li; Xu Tan; Yuejin Tan; Xin Lu (Physica A: Statistical Mechanics and its Applications, 2020)
Tree layouts are among the key approaches for network visualization, and are of particular importance for exploring the hierarchical structure of networks. However, visualizations of the overall network structure and its hierarchical relationships can rarely be optimized simultaneously. This paper presents a radial layout algorithm called PLANET that enables users to explore the network structure from a root node, while maintaining readability. In order to distribute the nodes evenly and minimize edge crossings, we define a list of angle assignment rules for displaying child nodes which can automatically maximize the tunable angles between parent and child nodes, and to uniformly divide the angles of child nodes. Using these rules, the structural properties of the network such as hubs can be properly conveyed, and the readability of nodes that are far from the root can be guaranteed. Our experimental results show that PLANET is comparable to similar algorithms in terms of execution time, and gives better performance in terms of node distribution, variance of edge length and number of edge crossing; these advantages become greater for networks with large diameters.